Corruption in China’s economic reform: a review of recent observations and explanations - Yu, Olivia (Crime, law and social change, 2008)
Corruption is a universal phenomenon of public institutions. It is markedly more pervasive in developing and transitional societies. China, with rapid economic growth for two decades, has been deeply troubled by the problem of official corruption at all levels in the public sector. The paper reviews the literature in the last 15 years which examines Chinese corruption from either a theoretical or empirical approach, by qualitative or quantitative methods in observation. Based on more than 30 studies with a focus on the related topic, the review covers issues of Chinese corruption data and statistics, theoretical explanations and China’s strategies of fighting corruption as well as critique.